Efficacy and safety of BVAC-C in HPV type 16- or 18–positive cervical carcinoma who failed 1st platinum-based chemotherapy: a phase I/IIa study - Choi, Chel Hun; Lee, Jeong-Won; Bae, Duk-Soo; Kang, Eun-Suk; Cho, Duck; Kim, Yong-Man; Kim, Kidong; Kim, Jae-Weon; Kim, Hee Seung; Kim, Young-Tae; Lee, Jung-Yun; Lim, Myong Cheol; et al. (Frontiers in Immunology, 2024)
Background BVAC-C, a B cell– and monocyte-based immunotherapeutic vaccine transfected with recombinant HPV E6/E7, was well tolerated in HPV–positive recurrent cervical carcinoma patients in a phase I study. This phase IIa study investigates the antitumor activity of BVAC-C in patients with HPV 16– or 18–positive cervical cancer who had experienced recurrence after a platinum-based combination chemotherapy. Patients and methods Patients were allocated to 3 arms; Arm 1, BVAC-C injection at 0, 4, 8 weeks; Arm 2, BVAC-C injection at 0, 4, 8, 12 weeks; Arm 3, BVAC-C injection at 0, 4, 8, 12 weeks with topotecan at 2, 6, 10, 14 weeks. Primary endpoints were safety and objective response rate (ORR) as assessed by an independent radiologist according to Response Evaluation Criteria in Solid Tumors version 1.1. Secondary endpoints included the disease control rate (DCR), duration of response (DOR), progression-free survival (PFS), and overall survival (OS). Results Of the 30 patients available for analysis, the ORR was 19.2% (Arm 1: 20.0% (3/15), Arm 2: 33.3% (2/6), Arm3: 0%) and the DCR was 53.8% (Arm 1: 57.1%, Arm 2: 28.6%, Arm3: 14.3%). The median DOR was 7.5 months (95% CI 7.1–not reported), the median PFS was 5.8 months (95% CI 4.2–10.3), and the median OS was 17.7 months (95% CI 12.0–not reported). All evaluated patients showed not only inflammatory cytokine responses (IFN-γ or TNF-α) but also potent E6/E7-specific T cell responses upon vaccinations. Immune responses of patients after vaccination were correlated with their clinical responses. Conclusion BVAC-C represents a promising treatment option and a manageable safety profile in the second-line setting for this patient population. Further studies are needed to identify potential biomarkers of response. Clinical trial registration ClinicalTrials.gov, identifier NCT02866006.